AN INTRODUCTION TO RADIOACTIVITY IN THE MARINE ENVIRONMENT - Wahyu Retno Prihatiningsih (Buletin Limbah, 2009)
1. Introduction Awareness of exposure to natural radioactivity and its technological enhancement in marine systems is growing. However, common misconceptions are the association of radioactive discharges only with the nuclear industry and that radioactivity is somehow unnatural. Environmental radioactivity is a natural occurrence, it was the combination of nuclear reactions and radioactivity that created all matter and variations in the stability of nuclides determined which elements are abundant and which are rare in the universe. Of the more than 5000 atoms (nuclides) known, about 95% are radioactive - they are the norm rather than the exception. Virtually all materials and environments on our planet are both radioactive and naturally exposed to ionising radiation. The energy from nuclear decay powers major geological changes on the Earth, such as internal convection cycles, earthquakes, volcanic activity and continental drift. Natural radioactivity triggers and catalyses key stages in the evolution of life and fusion reactors, such as our sun, provide the essential energy to our planet in the form of light and heat which regulates climate.